-1,3(7+4x)–11 =-4,5
-9,1-5,2х-11 =-4,5
-5,2х=-4,5+11+9,1=-4,5+20,1
-5,2х=15,6÷(-5,2)
х=-3
Пошаговое объяснение:
-1,3(7+4x) – 11 = -4,5
-1,3(7+4x) = 11 - 4,5
-1,3(7+4x) = 6,5
7+4x = 6,5 : (-1,3)
7+4x = -5
4x = -5 - 7
4x = -12
x = -12:4
x = -3
-1,3(7+4x)–11 =-4,5
-9,1-5,2х-11 =-4,5
-5,2х=-4,5+11+9,1=-4,5+20,1
-5,2х=15,6÷(-5,2)
х=-3
Пошаговое объяснение:
Пошаговое объяснение:
-1,3(7+4x) – 11 = -4,5
-1,3(7+4x) = 11 - 4,5
-1,3(7+4x) = 6,5
7+4x = 6,5 : (-1,3)
7+4x = -5
4x = -5 - 7
4x = -12
x = -12:4
x = -3